ANALISIS KEPUASAN WISATAWAN MANCANEGARA TERHADAP KUALITAS LAYANAN VIAVIA TRAVEL - , ANGGRAITA AJENG R. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Foreign Tourist Satisfaction with Services Quality of ViaVia Travel. Tourism Departement Sekolah Vokasi Universitas Gadjah Mada Yogyakarta. The problem concerning services quality in a company with customers satisfaction has become an important thing in the service companies, not exception ViaVia Travel to improve quality of customers satisfaction. This final report is about Foreign Tourist Satisfaction with Services Quality of ViaVia Travel. The purpose of this report is to find out the satisfaction foreign tourists level with quality service from ViaVia Travel. To find out foreign tourist consumers attitude with ViaVia Travel service. To find out obstacles faced by ViaVia Travel and their impact for customers. The method used in this final report is the descriptive qualitative, that is by observing, collecting data, analyzing, and concluding. Data were obtainedby giving questionares to the tourists who came over, then observing directly as the internship in ViaVia was carried out for 3 months. As a results show that the foreign tourists feel very satisfied with the quality of services from ViaVia Travel through staff performance, the product which is offered, tourguide services in guiding and direct tourists. There is impact, or influence for a customers: foreign tourists want to go back to feel another tours in the near future. However here, there are few obstacles faced by viavia travel. There are time availability from tourguide and the occurrence of misscomunication between staff and tourguide.